High Order Fixed Point and Newton's Methods in Banach Space. (17th February 2021) - Dubeau, François
Abstract: Through Taylor's expansions and a thorough analysis of the necessary and sufficient conditions that will entail for fixed point and Newton's iterative methods to be of higher order convergence in Banach space, we are able to present a unified way to make these methods faster. Numerical examples illustrate the theoretical results.